Exploring the Evolution of Budgeting Practices from Traditional to Technology - Sonjaya, Yaya (Advances in Management & Financial Reporting, 2024)
Purpose: This study explores the evolution of budgeting practices from traditional to contemporary technology-driven approaches. It examines how technological advancements and organizational changes have transformed budgeting processes, highlighting the shift towards more flexible and data-driven methodologies. Research Design and Methodology: This study embarks on a journey of comprehensive literature review using a qualitative research approach. The methodology involves systematic searches of academic databases, thematic analysis and synthesis of findings from relevant studies. The research focuses on the design, implementation, and impact of both traditional and modern budgeting practices, as well as the challenges associated with technological adoption. Findings and Discussion: The findings reveal that traditional budgeting methods, characterized by hierarchical and fixed targets, must be revised in dynamic business environments. Technological innovations, such as ERP systems and cloud-based platforms, significantly improve efficiency, accuracy, and decision-making. Alternative frameworks like the Balanced Scorecard and Beyond Budgeting promote strategic alignment and organizational agility. However, challenges such as data security, integration complexities, and resistance to change remain significant barriers to full adoption. Implications: This study's findings have direct and practical implications for financial managers and policymakers seeking to optimize budgeting processes. Investing in robust data infrastructure and fostering a culture of continuous improvement is essential for leveraging the benefits of technological innovations. Future research should focus on the long-term impacts of these practices and explore strategies to overcome implementation challenges. This will help organizations achieve greater agility, responsiveness, and competitiveness in an increasingly digitalized business landscape.